Pemulihan Ruang Belajar Pascabencana Banjir melalui Pendekatan Seni Partisipatif Berbasis Budaya Lokal Aceh di SMAN 1 Meureudu - Niko Andeska; Nurul Aida; Nisa Anggraini Batubara; Rahmawati; Destri Wulanda (Yayasan Pemimpin Inovasi Science, 2026)
Flood disasters significantly affect the education sector by damaging school facilities, disrupting learning activities, and reducing students’ psychosocial well-being. Following the flash flood that struck Meureudu, Pidie Jaya Regency, Aceh, in November 2025, SMAN 1 Meureudu experienced deterioration of its learning environment and an accumulation of plastic waste. This community service program aimed to restore the learning environment through a participatory art approach based on Acehnese local culture while promoting environmental awareness through plastic waste recycling. A participatory and collaborative approach was implemented involving 30 students divided into five groups. The program consisted of socialization, training, production of educational craft panels, mentoring, evaluation, and sustainability planning. Plastic waste was transformed into five educational craft panels (60 × 80 cm) using a simple thermal lamination technique with an iron and a heat gun. The panels incorporated environmental messages, disaster awareness, Acehnese cultural ornaments, and local language expressions before being installed in classrooms. The program improved the visual quality of learning spaces, enhanced students’ environmental awareness, creativity, and collaboration, and strengthened appreciation of Acehnese cultural identity. This approach demonstrates the potential of participatory art as an innovative and replicable model for post-disaster school recovery and environmental education.